THE RELATIONSHIP BETWEEN EXPOSURE TO TEXTISM AND SPELLING COMPETENCY - Ramaoka, Sekgalabje Isaiah; Kekana, Tebogo Johannes; Montle, Malesela (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
The purpose of the study was to investigate the relationship between exposure to textism and spelling competency. A quasi-experimental research design was used to determine how the independent variable (exposure to textism) influenced the dependent variable (spelling competency). A purposive sampling technique was employed to select 92 Grade 10 learners for the study. A preliminary questionnaire was administered to gather information about the learners’ cell phone ownership and text messaging behavior, and to further divide the sample into Experiment and Control groups. The Experiment group comprised learners who owned a smartphone and participated in text messaging, while learners who did not own a cell phone and were not actively involved in text messaging were assigned to the Control group. Data collection involved a dictation exercise and a creative writing task. The results of the dictation task showed a positive correlation between exposure to textism and spelling competency. Participants in the experiment groups, who owned a smartphone and were actively involved in text messaging, outperformed those in the control group, who did not own a cell phone or participate in text messaging. However, the results of the creative writing task presented a mixed trajectory of findings. Although the Experiment group performed better than the Control group in terms of incorrect spelling frequency, wrong word/class usage, and word omission, they also registered a higher count of punctuation-based spelling errors, word-spacing errors, and textism forms.